A contribution of N.A.Semashko to the development of medical prevention in Russia (to the 140-th anniversary of the birth) - V. A. Reshetnikov; Yu. V. Nesvizhsky; N. A. Kasimovskaya (Сеченовский вестник)
The article marks 140 years since the birth of the outstanding health organizer Nikolai Aleksandrovich Semashko, who made a huge contribution to the development of preventive health care system in Russia.